Inequality and Digitally Mediated Communication: Divides, Contradictions and Consequences. Issue 2 (3rd April 2017) - Mansell, Robin
Abstract : This article examines relationships between economic and social inequality and digitally mediated communication. Differences between instrumental and critical approaches in the digital divide literature are considered to highlight the limitations of the former approaches and the ways these are reflected in European policy. What we know about the relationship between technological innovation and society and its consequences for economic and social inequality is summarised and emerging expressions of inequality between humans and their digital machines are discussed. With computational models, algorithms and machine learning becoming more pervasive, it is argued that human beings are at risk of losing the ability to control the digitally mediated environment. Policy measures create incentives for small shifts in corporate digital platform strategy that amount to tinkering with the overall direction of technological innovation. The article emphasises the need for an inclusive dialogue to reveal potential alternative directions that might take better account of what people value in their digitally mediated lives.